Legal Consequences of a Binding Agreement for the Sale and Purchase of Land Rights Based on a Debt Agreement Between the Parties - Putri Damayanti, Tasya; Umu Adilah, Siti (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
Land is an important component of social life in Indonesia. Land can be utilized through rights granted to its legal subjects. This study aims to analyze the legal consequences of land sale and purchase agreements based on debt agreements for the parties, and to further analyze the notary's responsibility for land sale and purchase agreements based on debt relationships. The method used is empirical juridical, empirical legal research that combines normative legal analysis (statutory regulations) with empirical data from the field (social reality) to understand society. The results of the study show that the legal consequences of the agreement to bind the sale and purchase of land rights based on a debt agreement between the parties based on debt is null and void because it violates the objective requirements of validity and the responsibility of the Notary in making the deed. The Notary is fully responsible for the formal and material truth of the deed he made, ensuring that the deed reflects the actual situation and is in accordance with the law (PPJB) which is based on debt relationships which are often used as collateral for repayment (collateral) by creditors, but is high risk because it is not an official mortgage guarantee.